The Impact of Medication Adherence on Total Treatment Costs in Patients with Non-Small Cell Lung Carcinoma - Jessica Nathania; Santi Purna Sari; Yovita Diane Titiesari (Jurnal Respirologi Indonesia, 2026)
Background: Lung cancer is the leading cause of cancer-related death globally and ranks second in cancer incidence in Indonesia. Targeted therapies such as Epidermal Growth Factor Receptor-Tyrosine Kinase Inhibitors (EGFR-TKIs) and Anaplastic Lymphoma Kinase (ALK) inhibitors are recommended for advanced-stage non-small cell lung cancer (NSCLC) but may be limited by high cost. This study aimed to assess the relationship between medication adherence—measured by the mean proportion ratio (MPR)—and total treatment costs, and to examine its association with patient-specific factors. Methods: This observational, cross-sectional study used secondary data from NSCLC patients treated with EGFR-TKIs or ALK inhibitors at a Cancer Center in Jakarta, Indonesia (January 2023-March 2025). Eighty-six eligible patients (aged ≥18 years) were diagnosed with NSCLC, confirmed by immunohistochemistry (EGFR or ALK-positive). MPR measured medication adherence and analysed using Mann-Whitney and chi-square tests using SPSS Version 23, with a value of P<0.05 being significant. Results: Among NSCLC patients, about 89.53% exhibited a high level of treatment adherence, with an MPR score ≥0.8. Most patients were female (62.8%), under 60 years old (51.2%), stage IV (74.4%), and had an EGFR exon 19 mutation (52.3%). Osimertinib (30.2%) and Afatinib (24.4%) were the most used therapies. Most patients reported no serious side effects (57.0%) and received caregiver support (57.0%). There was no significant association between medication adherence and treatment cost (P=0.955), nor patient-related factors. Conclusion: Approximately 9 out of 10 NSCLC patients adhere to treatment with EGFR-TKIs or ALK inhibitors. High levels of adherence did not significantly increase additional medical expenses that would raise the total cost of treatment. Further qualitative research is needed to explore adherence determinants.